Mobilisasi Wisatawan Asing Terhadap Potensi Ancaman Non Tradisional Di Indonesia - Laode Muhammad Fathun (Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This paper aims to explain the problem is getting the massive influx of foreign tourists to Indonesia. Massive foreign tourists to Indonesia appeared to have an impact on the potential threat of non-traditional Indonesia. The number of foreign travelers resulted by the government to capitalize on the object of the tourism industry as one of the country's foreign exchange objects. With the method of qualitative analysis supported by data collection techniques secondary and primary then produced the conclusion that the massive rating aving to Indonesia because of a) policies shaft maritime Jokowi as one of orientation is the development of the tourism industry, b) bilateral relations between Indonesia and a number of countries is getting more intense including in the field of pariwisatwa, trade, investment, energy, etc., c) the geopolitical posture especially Indonesian mainly sea access easier for foreign tourists to visit Indonesia, including the illegal way. The result is a policy response one BVK make many visits to Indonesia. The impact potentially against illegal behavior in the form of non tradisionaal threat of the emergence of illegal labor. This is related to the inability of the state to provide employment for its citizens but to take the labor of other countries. Thus, the policy of rating mobilization efforts should be supervised by all sides because of the potential not only to the emergence of foreign workers but other illegal behavior such as drug dealers.